Analysis of the effects of antifungal peptide P-1 from Bacillus pumilus HN-10 on energy metabolism of Trichothecium roseum. (June 2022) - Wu, Shujuan; Yun, Jianmin; Wang, Rui; Zhang, Wenwei; Hao, Lin; Pei, Pengzheng
Abstract: This study investigated the antifungal activity and possible mode of action of Bacillus pumilus HN-10 antifungal peptide P-1 against Trichothecium roseum . The results showed that the antifungal peptide P-1 at a concentration of 1.0 μg mL -1 had strong antifungal activity against T. roseum . P-1 inhibited the tricarboxylic acid cycle (TCA) pathway and the transporter pathway of NADH to coenzyme Q on the electron transport chain. P-1 significantly reduced succinate dehydrogenase (SDH), malate dehydrogenase (MDH), ATPase, mitochondrial complex enzymes I, II and IV enzyme activities on the electron transport chain, and 5'-triphosphate (ATP), 5'-diphosphate (ADP), 5'-monophosphate (AMP) content, and energy charge (EC); significantly increased 6-phosphofructokinase (PFK) enzyme activity. The release of Ca 2+ (OD680 ) from the inner mitochondrial membrane and the openness of the mitochondrial permeability transition pore (MPTP) were analysed, and microscopy was performed following staining of mitochondria with JC-1. The results indicated that P-1 significantly increased the release of Ca 2+ and the openness of MPTP, decreased the mitochondrial membrane potential, and produced green fluorescence; transcriptomics data analysis showed that there were 39 differentially expressed genes ( DEGs ) related to energy metabolism enzymes. The results verified by qRT-PCR were basically consistent with the transcriptome sequencing results. Thus, P-1 achieved its inhibitory effect mainly by regulating genes related to energy metabolism. Highlights: P-1 inhibited the tricarboxylic acid cycle and the transporter pathway of NADH to coenzyme Q on the electron transport chain. P-1 destroys the structure of the mitochondrial membrane. P-1 alter mRNA transcription levels of energy metabolism-related enzymes.